Sex-specific differences in the associations between adiposity indices and incident hyperuricemia among middle-aged and older adults: a nationwide longitudinal study - Liu, Zhiyi; Zhou, Qinwu; Tang, Yuqiong; Li, Jiyong; Chen, Qiutong; Yang, Hongguang; Zhou, Shuhan (Frontiers in Endocrinology, 2024)
Objective: Although Obesity was a known risk for hyperuricemia (HUA), the associations between adiposity indices and incident HUA and whether the sex-specific differences existed was still unknown. We aimed to investigate the associations of adiposity indices and incident HUA in a longitudinal study.: Data from CHARLS in 2011-2012 and 2015-2016 was used to conducted a cohort study. Participants aged ≥ 45 years old without HUA at baseline were included in this study. Adiposity indices, including body mass index (BMI), waist circumference (WC), waist-to-height ratio body roundness index (BRI), conicity index (CI), lipid accumulation product (LAP) index, waist-to-height ratio (WHtR), visceral adiposity index (VAI), and Chinese visceral adiposity index (CVAI) were calculated. Logistic analysis was used to analyze the association between adiposity indices and incident HUA risk stratified by gender. Receiver operating characteristic curve analysis was performed to evaluate the power of predictions for incident HUA.Results: Of 5,873 participants aged 59.0 ± 8.7 years enrolled in this study, 578 (9.8%) participants developed HUA during the 4-year follow-up period. After adjusting for confounding variables, LAP, VAI and CVAI showed significant association with incident HUA. BMI, WC, WHtR, BRI and CI were significantly associated with incident HUA in females but not in males. LAP had the highest AUC (0.612), followed by CVAI (0.596) in males, while CVAI had the highest AUC (0.707), followed by LAP (0.691) in females. All indices showed better predictive ability in females than in males.Our findings indicated adiposity indices were effective predictors of incident HUA and adiposity indices showed better predictive power in females than males. In clinical practice, adiposity indices could be used to assess and prevent incident HUA among Chinese middle-aged and older adults.